Production and spray drying of protein hydrolyzate obtained from tilapia processing by-products - De Paris, Leandro Daniel; Adams Haab, Júlio César; Sary, Cesar; Bernardi, Daniela Miotto; Boscolo, Wilson Rogério; Signor, Altevir (Acta Scientiarum. Technology, 2016)
In the last few decades, the offer of by-products obtained from the processing of tilapia (Oreochromis niloticus) has increased, and the need for developing products with high biological and nutritional values for use in animal nutrition motivated this study. Enzymatic hydrolysis of carcass, head and skin of tilapia was performed, as well as the separation of oil, residual solids and soluble proteins by centrifugation at high temperature and the spray drying of the protein fraction. Factorial designs were employed in the assays to evaluate the operating conditions of the spray dryer (inlet and outlet temperatures and flow rate) and the inclusion of drying aid agents (maltodextrin and calcium carbonate). The spray drying showed the best results with air inlet temperature of 190ÂºC, outlet temperature of 90ÂºC, flow rate of 30 LÂ·h-1 including 10% maltodextrin (mass) in the liquid feed as a drying aid. The final powder recovery was higher than 90% and the physical, chemical and microbiological analyses met the Brazilian legal standards. Â